(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The development of professional competence in future doctors is a strategic educational goal in modern medical education. Acmeology, as an interdisciplinary science focused on personal and professional self-realization and excellence, offers a powerful methodological framework for achieving this goal. The integration of acmeological principles into the training process helps to identify the optimal pedagogical conditions for fostering professional growth, self-reflection, and lifelong learning skills in medical students. This article explores the theoretical foundations of acmeology in relation to competence-based education and substantiates the pedagogical mechanisms required to develop high-level professional competencies in future doctors.